PENGARUH MANAGEMENT CONTROL SYSTEM TERHADAP CUSTOMER ORIENTED MEASURES MELALUI EMPLOYEE ORIENTED MEASURES SEBAGAI VARIABEL INTERVENING - David Sasmita; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aimed to examine the direct affect of management control system to customer oriented measures; management control system to employee oriented measures; indirect affect of management control system to customer oriented measures through employee oriented measures in public companies in Indonesia. This study used a quantitative approach, and the data were obtained by distributing questionnaires to public companies in Indonesia. Then the data obtained were processed by using smartPLS software. This study showed that there was a positive relationship of management control system to customer oriented measures, positive relationship of management control system to employee oriented measures, and positive relationship of employee oriented measures to customer oriented measure in public companies in Indonesia.